2021
DOI: 10.1364/ao.443630
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-interrogated magnetic sensor based on S-tapered and multimode fiber integrated with ferrofluids

Abstract: In this study, a high-sensitivity intensity-interrogated fiber sensor integrated with ferrofluids is proposed for the measurement of a weak magnetic field (MF) with resolved temperature cross-sensitivity. The MF sensor is fabricated simply by an offset tapering single-mode fiber concatenated with a multimode fiber (MMF), which is then encapsulated into a capillary tube filled with ferrofluids. In the presence of MMF, stronger mode coupling could be achieved over the S-tapered fiber region. Its spectral respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, we can provide a few examples of widely utilized MMF sensors to illustrate the boundless applicability of MMF sensors. These include magnetic field sensing [112][113][114][115][116], distributed acoustic sensing [117], fluidic flow measurement [118], steel corrosion monitoring [119], relative humidity (RH) sensing [120][121][122], gas pressure sensing [103,123,124], and volatile organic compound (VOC) gas detection [125,126]. Table 6 provides a summary of the key parameters for the sensors discussed.…”
Section: Other Sensorsmentioning
confidence: 99%
“…However, we can provide a few examples of widely utilized MMF sensors to illustrate the boundless applicability of MMF sensors. These include magnetic field sensing [112][113][114][115][116], distributed acoustic sensing [117], fluidic flow measurement [118], steel corrosion monitoring [119], relative humidity (RH) sensing [120][121][122], gas pressure sensing [103,123,124], and volatile organic compound (VOC) gas detection [125,126]. Table 6 provides a summary of the key parameters for the sensors discussed.…”
Section: Other Sensorsmentioning
confidence: 99%
“…For the sensor’s miniaturization and integration, intensity-modulated fiber-optic magnetometers are preferable. To realize intensity-demodulated magnetometers, Duan et al [ 15 ] reported a fiber-optic magnetometer based on x zcS-tapered and multimode fiber, whose sensitivity is up to 1.130 dB/mT in 4–12 mT. Lu et al [ 16 ] designed a fiber-optic magnetometer by using single serial-tilted-tapered fiber functionalized with magnetic fluid.…”
Section: Introductionmentioning
confidence: 99%